Selectively Halogenated Flavonolignans-Preparation and Antibacterial Activity - Hurtová, Martina; Káňová, Kristýna; Dobiasová, Simona; Holasová, Kateřina; Čáková, Denisa; Hoang, Lan; Biedermann, David; Kuzma, Marek; Cvačka, Josef; Křen, Vladimír; Viktorová, Jitka; Valentová, Kateřina (International journal of molecular sciences, 2022)
A library of previously unknown halogenated derivatives of flavonolignans (silybins A and B, 2,3-dehydrosilybin, silychristin A, and 2,3-dehydrosilychristin A) was prepared. The effect of halogenation on the biological activity of flavonolignans was investigated. Halogenated derivatives had a significant effect on bacteria. All prepared derivatives inhibited the AI-2 type of bacterial communication (quorum sensing) at concentrations below 10 µM. All prepared compounds also inhibited the adhesion of bacteria (Staphyloccocus aureus and Pseudomonas aeruginosa) to the surface, preventing biofilm formation. These two effects indicate that the halogenated derivatives are promising antibacterial agents. Moreover, these derivatives acted synergistically with antibiotics and reduced the viability of antibiotic-resistant S. aureus. Some flavonolignans were able to reverse the resistant phenotype to a sensitive one, implying that they modulate antibiotic resistance.
Keywords: halogenation; Bacteria; Biofilms; flavonolignans; Pseudomonas aeruginosa; bacteria; Quorum Sensing; Anti-Bacterial Agents; multidrug resistance; flavonoids; antibakteriální látky; biological activity; methicilin rezistentní Staphylococcus aureus; Methicillin-Resistant Staphylococcus aureus; quorum sensing; biofilmy